The relationship between probing bone loss and standardized radiographic analysis - (:unkn) unknown (My University, 1998)
This study evaluated the validity of radiographic alveolar bone defect depth measurements to direct probing measurements. The study was planned in two parts. The first part consisted of the evaluation of artificially prepared defects in dry mandibles. These consisted of 3-mm intrabony defects created at the mesial aspect of the second mandibular molar and a Class II furcation defect on the buccal aspect of the first molar. A total of six standardized periapical radiographs with grids were obtained. They were then evaluated by 10 independent examiners who recorded the distance between the alveolar crest (AC) or root junction (RJ) and base of defect (BD) in the proximal and furcation areas of the teeth. Intra- and inter-examiner differences were assessed. Radiographic results showed that these measurements overestimated the mean defect depth values within 0.12 mm in intrabony defects and underestimated within 0.40 mm in Class II furcation defects. The differences between the radiographic and direct dry mandible defect depth measurements were found to be statistically significant (P < .05) with correlation values r = .50 and r = .46, respectively. The clinical part of the study included evaluation of 64 preoperative radiographs taken from patients who underwent various types of periodontal surgery. Mean clinical bone defect depth was found to be 4.20 mm and the mean of the radiographic defect depth measurements was found to be 3.92 mm in intrabony defects. In furcation defects these values were 3.92 mm and 3.55 mm, respectively. The results revealed that (1) a strong correlation existed between the radiographic and clinical assessments in both type of defects (r = .85, P < .001), and that (2) the difference between the two types of assessment methods was generally within 1 mm (58%). It can be concluded that in both dry mandible and clinical studies radiographic interpretation of the intrabony and furcation defects showed differences from the actual bone defect depths.
Keywords: Adult; Humans; Middle Aged; Reproducibility of Results; Mandible; Alveolar Bone Loss; Statistics, Nonparametric; Periodontal Attachment Loss; Periodontitis; Radiography, Dental; Furcation Defects; Observer Variation